Women Empowerment and Economic Development - Duflo, Esther (Journal of Economic Literature, 2012)
Women empowerment and economic development are closely related: in one direction, development alone can play a major role in driving down inequality between men and women; in the other direction, empowering women may benefit development. Does this imply that pushing just one of these two levers would set a virtuous circle in motion? This paper reviews the literature on both sides of the empowerment—development nexus, and argues that the interrelationships are probably too weak to be self-sustaining, and that continuous policy commitment to equality for its own sake may be needed to bring about equality between men and women. (JEL I14, I24, I32, I38, J13, J16, O15)